Identification of KLF3 gene polymorphism in Indonesian Friesian Holstein cattle - Agung, P. P.; Laoditta, F. (Diponegoro University, 2018)
The KLF3 gene was a potential genetic marker candidate due to its involvement in many biological processes such as cell proliferation, cell differentiation, and apoptosis. This study was conducted to identify the KLF3 gene polymorphism in the Indonesian FH cattle. A total of 302 individual cattle blood samples from West Java (n=138), Central Java (n=34), and East Java (n=130) provincies were used to obtainDNA samples. The DNA sequencing was performed using 9 samples (each location of sampling represented by 3 samples) for initial identification of the KLF3 gene polymorphismand followed by PCR-RFLP analysis using all DNA samples. There were two SNPs identified in the intron region of the KLF3 gene i.e. SNP g.59607486delC and SNP g.59607554A>G. The SNP g.59607554A>G could be detected using PCR-RFLP method with HpyCH4IV restriction enzyme and resulted three genotypes of the KLF3 gene (AA, AG, and GG) but its heterozygosity value was low in the Indonesian FH cattle. The AA genotype has the highest frequency (0.73), while the AGand GG genotypes frequency were 0.24 and 0.03, respectively. Information about the KLF3 gene polymorphism in this study can be considered for further study to analyse its association with milk and protein yield traits.